Precision medicine and cardiology - Pitt, Geoffrey S. (Henry Stewart Talks, 2016)
Precision medicine, Precision medicine to personalized medicine, Personalized cardiovascular medicine, Mutation specific therapy, CFTR mutations, Targeted cancer therapies, Genotype: specific therapy in cardiology, Long QT syndrome genetics, Move from Mendelian genetics to complex traits, Variant of uncertain clinical significance (VUS), Precision medicine is aiming for the right drug in the right dose at the right time